The futures of anticipatory reason: Contingency and speculation in the sting operation. (August 2019) - Hong, Sun-ha; Szpunar, Piotr M
This article examines invocations of the future in contemporary security discourse and practice. This future constitutes not a temporal zone of events to come, nor a horizon of concrete visions for tomorrow, but an indefinite source of contingency and speculation. Predictive, preemptive and otherwise anticipatory security practices strategically utilize the future to circulate the kinds of truths, beliefs, claims, that might otherwise be difficult to legitimize. The article synthesizes critical security studies with broader humanistic thought on the future, with a focus on the sting operations in recent US counter-terrorism practice. It argues that the future today functions as an 'epistemic black market', a zone of tolerated unorthodoxy where boundaries defining proper truth-claims become porous and flexible. Importantly, this epistemic flexibility is often leveraged towards a certain conservatism, where familiar relations of state control are reconfirmed and expanded upon. This conceptualization of the future has important implications for standards of truth and justice, as well as public imaginations of security practices, at a time of increasingly preemptive and anticipatory securitization.